Multimodal Imaging Techniques for the Extraction of Detailed Geometrical and Physiological Information for Use in Multi-Scale Models of Colorectal Cancer and Treatment of Individual Patients. Issue 2 (2006) - Pitt-Francis, Joe; Chen, Dan; Slaymaker, Mark; Simpson, Andrew; Brady, Michael; van Leeuwen, Ingeborg; Reddington, Fiona; Quirke, Phil; Brown, Gina; Gavaghan, David
Abstract : A vast array of mathematical models have been proposed for all stages of cancer formation across a wide range of spatio–temporal scales. Attention is now turning to coupling these models across scales and building models of "virtual tumours" for use in in silico testing of novel drugs and treatment regimes. This leads naturally to the requirement for detailed knowledge of the underlying geometry and physiological properties of individual tumours for use in: (i) multi-scale mathematical models of in vivo tumour growth and development; (ii) fusion of multi-scale, multimodal medical imaging techniques to improve the diagnosis and treatment of individual patients; and (iii) training of cancer specialists and surgeons.